FRÊNULO LINGUAL: ALEITAMENTO MATERNO E MANIFESTAÇÕES CLÍNICAS ASSOCIADAS - COTLINSKY, SOLANGE CRISTINA COSTA (2021)
Ankyloglossia is a congenital anomaly characterized by a small portion of embryonic tissue that did not undergo apoptosis during development and remained on the ventral side of the tongue. Ankyloglossia is often identified as one of the factors that negatively influence breastfeeding. However, it is clear, in clinical practice, that ankyloglossia involves other symptoms in addition to breastfeeding. Objectives: to verify the relationship between the anatomy of the lingual frenulum and breastfeeding in newborns, in addition to other clinical manifestations in children. Method: this is a descriptive, cross-sectional, quantitative study. Data were collected at the SUS childcare service in the municipality of Guarapuava. To assess the frenulum or frenulum, the Bristol Protocol was used. The other variables were obtained from interviews carried out with the mothers, as well as from pediatric clinical examination. Results: ankyloglossia was present and associated with clinical manifestations, verifying the difficulty in sucking and other symptoms, such as nausea, reflux, cramps, postural, respiratory and weight loss. Conclusion: ankyloglossia had a negative impact on the relationship with breastfeeding and may have caused other symptoms in children. New studies need to be carried out to elucidate these relationships.